Composite graphite coated product, graphite composite material and preparation method and application thereof

By performing secondary coating on the graphite surface and using asphalt, anthracene oil and resin to form a dense coating layer, it solves the problems of poor toughness and many side reactions of carbon coating, and improves the lithium-ion battery Electrochemical properties and stability.

CN114050238BActive Publication Date: 2025-02-14SHANGHAI SHANSHAN TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111242004.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-25
Publication Date
2025-02-14
Estimated Expiration
2041-10-25

AI Technical Summary

Technical Problem

In the prior art, the toughness of the carbon cladding layer is poor, resulting in many side reactions in the circulation of lithium-ion batteries, affecting the stability and life of the battery.

Method used

By performing secondary coating on the graphite surface, composite graphite coated products are prepared by heat treatment and carbonization treatment by using coating agents such as asphalt, anthracene oil and resin to form a dense coating layer.

Benefits of technology

The first discharge efficiency, capacity retention and rate performance of graphite composite materials are improved, lithium ion consumption in electrode circulation is suppressed, and the high-temperature gas production phenomenon of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114050238B_ABST
    Figure CN114050238B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite graphite coating, a graphite composite material, and a preparation method and application thereof. The preparation method of the composite graphite coating comprises the following steps: (1) subjecting a mixture of single-particle artificial graphite A and coating agent A to heat treatment to obtain single-particle artificial graphite B; the coating agent A is asphalt and / or anthracene oil; the asphalt includes coal tar pitch and / or petroleum asphalt; (2) subjecting a mixture of single-particle artificial graphite B and coating agent B to carbonization to obtain a composite graphite coating; the coating agent B is one or more of asphalt, anthracene oil and resin; the asphalt includes coal tar pitch and / or petroleum asphalt; the carbonization temperature is 1200-1700°C. The graphite composite material containing the composite graphite coating of the present invention has the characteristics of a dense surface coating structure, and exhibits better first discharge efficiency, capacity retention rate and rate performance when used as a negative electrode material in lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite graphite coated product, a graphite composite material and a preparation method and application thereof. Background Art

[0002] At present, the existing technology mostly uses carbon coating methods to improve the conductivity of the electrode, such as coating a layer of precursor on the graphite surface by solid phase coating and liquid phase coating, and then carbonizing at high temperature. The coating layer structure obtained by this method is relatively complete, which not only improves the conductivity of the material but also protects the structure of the graphite itself. At the same time, the method is simple to operate and the cost of raw materials is low, and large-scale production is achieved. However, the toughness of this coating layer is poor, and the effects are as follows: if the coating layer is too thin, it is easy to break, and the broken coating material may cause more side reactions; if the coating layer is too thick, while increasing the specific surface area of ​​the graphite particles, it also increases the generation area of ​​the SEI film. After the film is formed, due to the barrier of the SEI film, the gas-producing solvent in the electrolyte fails to fully react with the graphite, and later under high temperature impact, the SEI film self-decomposes, and the gas-producing solvent contacts the graphite again to produce gas by side reactions, resulting in battery bulging.

[0003] In the prior art, the coating layer coated with organic polymers is not easy to break, but its conductivity is poor. Inorganic coating modification can improve the long-cycle performance of the material and the thickness of the coating layer is controllable, but there are problems of high cost and difficulty in mass production. For example, Chinese patent CN105514394B prepares graphite material by heating and drying a graphite mixture. The reaction has high energy consumption and high requirements on environmental conditions, and cannot meet the production of large-scale applications.

[0004] Therefore, it is necessary to study how to effectively inhibit the side reactions in lithium-ion battery cycles while maintaining the integrity of the graphite structure. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defects of poor toughness of the carbon coating layer and many side reactions in the battery cycle in the prior art, and provide a composite graphite coating product, a graphite composite material and its preparation method and application. The surface coating layer structure of the graphite composite material provided by the present invention is dense, and when used as a negative electrode material in a lithium ion battery, it exhibits better first discharge efficiency, capacity retention rate and rate performance.

[0006] The present invention solves the above technical problems through the following technical solutions.

[0007] The present invention provides a method for preparing a composite graphite coated product, which comprises the following steps:

[0008] (1) subjecting a mixture of single-particle artificial graphite A and coating agent A to heat treatment to obtain single-particle artificial graphite B; the coating agent A is asphalt and / or anthracene oil; the asphalt includes coal asphalt and / or petroleum asphalt;

[0009] (2) Carbonizing a mixture of single-particle artificial graphite B and coating agent B to obtain a composite graphite coating product; the coating agent B is one or more of asphalt, anthracene oil and resin; the asphalt includes coal tar and / or petroleum asphalt; the carbonization temperature is 1200-1700°C.

[0010] In step (1), the particle size of the single-particle artificial graphite A may be 7 to 12 μm, for example, 9 μm.

[0011] In step (1), the preparation method of the single-particle artificial graphite A can be conventional in the art, preferably, by graphitizing aromatic petroleum coke.

[0012] The graphitization operation may also include a pre-carbonization process, which can increase the graphitization loading (about 20%) and reduce the cost.

[0013] The pre-carbonization temperature may be 600-1300°C, for example 1050°C.

[0014] The pre-carbonization time may be 3 to 27 days, for example 4.5 days.

[0015] The pre-carbonization can be carried out in conventional carbonization equipment in the art, preferably a tunnel kiln, a ring furnace or a rotary kiln, such as a tunnel kiln.

[0016] The type of aromatic hydrocarbon petroleum coke can be conventional in the art, preferably green coke, such as Daqing petroleum green coke.

[0017] Preferably, the aromatic petroleum coke further includes a pretreatment process of crushing and premixing before graphitization.

[0018] Before the pretreatment, the specifications of the aromatic petroleum coke may be volatile matter ≤ 16%, and ash content ≤ 0.4%.

[0019] After the pulverization process, the particle size D50 of the aromatic petroleum coke may be 0 to 50 μm, preferably 9 to 10 μm, such as 9.1 μm.

[0020] After the pulverization process, the tap density of the aromatic petroleum coke can be 0.5 to 1.3 g / cm 3 , preferably 0.5 to 1.1 g / cm 3 , for example 0.54 g / cm 3 .

[0021] The pulverization can be carried out in conventional pulverization equipment in the art, such as a roller mill.

[0022] The graphitization temperature may be 2800-3050°C, for example 3000°C.

[0023] Wherein, the graphitization time may be 15 to 25 days, for example, 500 hours.

[0024] The graphitization processing cycle may be 35 to 45 days, for example 40 days.

[0025] The graphitization can be carried out in a conventional graphitization device in the art, such as a box furnace.

[0026] In the present invention, when the coating agent A and the coating agent B contain coal tar pitch, the types of the coal tar pitch can be conventional in the art and are independently selected, for example, coal tar pitch having a softening point of 80-280°C and a coking value of 40-80%, preferably carbon fiber spinnable asphalt, more preferably "asphalt having a softening point of 155°C and a coking value of 45%", "asphalt having a softening point of 205°C and a coking value of 60%" and "asphalt having a softening point of 275°C and a coking value of 75%" One or more; the "asphalt having a softening point of 155°C and a coking value of 45%" may be XM, the "asphalt having a softening point of 205°C and a coking value of 60%" may be XD, the "asphalt having a softening point of 275°C and a coking value of 75%" may be XH, and the best is XM and / or XD.

[0027] In the present invention, when the coating agent A and the coating agent B contain petroleum asphalt, the petroleum asphalt can be a petroleum asphalt with a softening point of 140-280°C and a coking value of 38-85%, and each is independently selected, for example, a petroleum asphalt with a softening point of ~280°C and a coking value of ~80%, and another example is XK.

[0028] Among them, at the same carbon residue amount, the weight ratio of XM, XD, XH and XK can be calculated according to the coking value, and the calculation formula is: carbon residue amount = coking value * asphalt weight / graphite weight.

[0029] In the present invention, when the coating agent A and the coating agent B contain asphalt, the residual carbon value of the asphalt in the coating agent A and the coating agent B may be 1 to 4 wt %.

[0030] In the present invention, when the coating agent A and the coating agent B contain anthracene oil, the coking value of the anthracene oil in the coating agent A and the coating agent B may be 11 to 20%.

[0031] In the present invention, when the coating agent A and the coating agent B contain anthracene oil, the residual carbon value of the anthracene oil in the coating agent A and the coating agent B may be 0.5 to 2 wt %.

[0032] In the present invention, when the coating agent B contains a resin, the resin in the coating agent B may be an epoxy resin and / or a phenolic resin, such as a phenolic resin; the coking value of the phenolic resin may be ˜38%, and the softening point of the phenolic resin may be ˜140° C.

[0033] In step (1), the amount of the coating agent A can be 1 to 11 wt %; % refers to the mass percentage of the coating agent A to the single particle artificial graphite A.

[0034] In step (2), the amount of the coating agent B can be 1 to 11 wt %; % refers to the mass percentage of the coating agent B in the single particle artificial graphite B.

[0035] In the present invention, the types of the coating agent A and the coating agent B can be the same or different; when they are the same, the coating agent A and the coating agent B can both be anthracene oil; when they are different, when the coating agent A is anthracene oil, the coating agent B can be phenolic resin, or when the coating agent B is anthracene oil, the coating agent A can be isotropic asphalt from XM or Capone manufacturers.

[0036] In a preferred embodiment of the present invention, when the coating agent A is anthracene oil and the amount used is 11 wt%, the coating agent B is anthracene oil and the amount used is 11 wt%.

[0037] In another preferred embodiment of the present invention, when the coating agent A is anthracene oil and the amount used is 11wt%, the coating agent B is phenolic resin and the amount used is 5wt%.

[0038] In another preferred embodiment of the present invention, when the coating agent A is XM, and the amount used is 6.5wt%, the coating agent B is anthracene oil, and the amount used is 11wt%.

[0039] In another preferred embodiment of the present invention, when the coating agent A is isotropic asphalt produced by Capone, and the dosage is 6.5wt%, the coating agent B is anthracene oil, and the dosage is 11wt%.

[0040] In step (1), the heat treatment temperature may be 550°C to 650°C, preferably 600°C to 650°C, for example 610°C.

[0041] In step (1), the heat treatment time may be 4 to 12 hours, for example 12 hours.

[0042] In step (1), the heat treatment can be carried out in a conventional heat treatment device in the art, such as a horizontal kettle.

[0043] In step (1), the heat treatment also includes fusion treatment before the heat treatment.

[0044] The fusion process can generally be carried out in a fusion machine or a VC mixer.

[0045] The fusion time may be a conventional time in the art, generally 5 to 30 minutes, such as 10 minutes.

[0046] In step (2), the carbonization temperature is preferably 1200-1400°C, for example 1350°C or 1400°C.

[0047] In step (2), the carbonization time may be 10 to 14 hours, for example 12 hours.

[0048] In step (2), the carbonization can be carried out in conventional carbonization equipment in the art, such as a roller kiln.

[0049] In step (2), the carbonization also includes a fusion treatment.

[0050] The fusion process can generally be performed in a fusion machine.

[0051] The fusion time may be a conventional time in the art, generally 5 to 30 minutes, such as 10 minutes.

[0052] The present invention also provides a composite graphite coated product, which is prepared by the above-mentioned preparation method.

[0053] The present invention also provides a composite graphite coated product, which is a core-shell structure, in which the core is graphite and the shell is a carbon coating layer, and the carbon coating layer includes a first carbon coating layer and a second carbon coating layer from the inside to the outside;

[0054] The first carbon coating layer is obtained by heat treating the coating agent A; the coating agent A and the heat treatment method are as described above;

[0055] The second carbon coating layer is obtained by carbonizing the coating agent B; the coating agent B and the carbonization method are as described above.

[0056] In the present invention, from inside to outside, inside refers to the area close to the graphite core, and outside refers to the area close to the carbon coating layer.

[0057] The present invention also provides a graphite composite material, wherein the outer layer of the composite graphite coated product is wrapped with a coating layer containing an organic small molecule salt.

[0058] In the present invention, the organic small molecule salt may be one or more of sulfonates, organic diacid salts and acrylates.

[0059] In the present invention, the content of the organic small molecule salt may be 0.5-2 wt %, where % refers to the mass percentage of the organic small molecule salt in the composite graphite coated product.

[0060] In the present invention, the organic small molecules in the salt coating layer can realize self-polymerization through electrocatalysis to form a dense coating layer with certain flexibility. Among them, the cations can change the electronic state inside the graphite, promote the embedding of ions in the lithium battery, and improve the charging performance.

[0061] The present invention also provides a method for preparing a graphite composite material, which comprises the following steps: uniformly mixing the composite graphite coated product and an organic small molecule salt solution; the relative molecular weight of the organic small molecule salt is <500.

[0062] In the present invention, the organic small molecule salt solution may be a mixed aqueous solution of one or more of sulfonates, organic diacid salts and acrylates.

[0063] The sulfonate may be one or more of sodium dodecylbenzenesulfonate, sodium 5-isophthalic acid sulfonate, sodium 3-carboxybenzenesulfonate, sodium p-aminobenzenesulfonate and sodium hydroxybenzenesulfonate, such as sodium 5-isophthalic acid sulfonate. The organic diacid may be sodium dodecyldiacid and / or sodium maleate.

[0064] When the organic diacid salt is sodium maleate, the concentration of the solution of the organic diacid salt is preferably 0.1-0.7M, such as 0.1M, 0.33M or 0.67M.

[0065] Wherein, the acrylate may be sodium acrylate.

[0066] When the acrylate is sodium acrylate, the concentration of the acrylate solution is preferably 0.3-0.7M, such as 0.33M or 0.67M.

[0067] In the present invention, the addition ratio of the organic small molecule salt is preferably 0.5-2wt%, where % refers to the mass percentage of the organic small molecule salt in the composite graphite coated product.

[0068] In the present invention, the concentration of the organic small molecule salt solution, calculated as small molecule salt, can be 0.1 to 1 mol / L, preferably 0.1 to 0.67 mol / L, such as 0.1 mol / L, 0.33 mol / L and 0.67 mol / L.

[0069] In the present invention, in the organic small molecule salt solution, the concentration of the composite graphite coated product can be 20-40wt%, where % refers to the mass ratio of the composite graphite coated product to the organic small molecule salt solution.

[0070] In the present invention, the pH of the organic small molecule salt solution is preferably neutral; if the pH is acidic, the organic acid will corrode the electrode material, increase the irreversible capacity of the electrode, and also corrode the SEI film of the graphite negative electrode; if the pH is alkaline, it is easy to make the active Li + Converted to LiOH, consuming Li + .

[0071] In the present invention, the mixing method can be conventional in the art, preferably, the mixing is performed uniformly by fusion treatment.

[0072] The fusion can be performed in conventional equipment in the art, such as a fusion machine.

[0073] The fusion frequency may be conventional in the art, such as 40 Hz.

[0074] The rotation speed of the fused main engine may be a conventional rotation speed in the art, generally 1200 r / min.

[0075] The fusion time may be conventional in the art, generally 5 to 30 minutes, preferably 6 minutes or 10 minutes.

[0076] Preferably, the fusion process also includes a post-processing of heating and drying.

[0077] The drying method can be conventional in the art, generally vacuum drying or forced air drying; when the drying method is vacuum drying, the drying temperature is preferably 80-110°C, for example 105°C; when the drying method is forced air drying, the forced air drying temperature is 70-130°C, for example 110°C.

[0078] The present invention also provides a graphite composite material, which is prepared by the above-mentioned preparation method.

[0079] The present invention also provides the use of the above graphite composite material as a negative electrode material in a lithium ion battery.

[0080] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0081] The reagents and raw materials used in the present invention are commercially available.

[0082] The positive and progressive effects of the present invention are:

[0083] (1) The present invention performs secondary coating on the graphite surface and adjusts the coating thickness by changing the amount of coating agent used; a layer of carboxyl functional groups is uniformly coated on the surface of the prepared composite graphite coated product to form a grid structure, which promotes the formation of a thin and dense SEI film with a certain elasticity. The prepared graphite composite material has the characteristic of a dense surface coating structure.

[0084] (2) When the graphite composite material prepared by the present invention is used as a negative electrode material in a lithium ion battery, it effectively improves the high-temperature gas generation phenomenon of the lithium ion battery and inhibits the lithium ion consumption in the electrode cycle; the tap compaction can be 0.80 to 1.01 g / cm 3 , D50 is 13.2μm, compacted density is 1.79~1.92g / cm 3 The first discharge efficiency is 95-96%, the capacity retention rate at 60°C is 87.8-90.5%, the total rate of 2C constant / 0.1C is 15.9-24.2%, and the DC resistance (DCIR) is as low as 3.58Ω.

[0085] (3) The preparation process of the present invention is simple, the reaction conditions are mild, and it is suitable for industrial-scale production. In addition, the modifier is safe and has a high utilization rate. The modification process has little pollution, which effectively reduces the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0086] Figure 1 Schematic diagram of the structure of graphite composite material.

[0087] Figure 2 This is a particle size distribution curve of the graphite composite material prepared in Example 1.

[0088] Figure 3 This is the SEM image of the graphite composite material prepared in Example 1. DETAILED DESCRIPTION

[0089] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0090] In the embodiment of the present invention, the volatile matter of the selected Daqing petroleum green coke is 10% and the ash content is less than 0.5%.

[0091] In the embodiments of the present invention, the asphalt selected has a softening point of 150-280° C., a coking value of 48-83%, and a residual carbon value of 1-4wt%.

[0092] In the embodiment of the present invention, the coking value of the anthracene oil selected is 11-20%, and the residual carbon value is 2wt%.

[0093] Example 1

[0094] (1) Daqing petroleum coke was crushed using a roller mill to a D50 of 9.1 μm and a tap weight of 0.54 g / cm 3 , pre-carbonized at 1050°C for 108h in a tunnel kiln, and then high-temperature graphitized at 3000°C in a box furnace. The graphitization time was 500h and the processing cycle was 40 days to obtain single-particle artificial graphite A with D50=9μm.

[0095] (2) 80 kg of the above-obtained single-particle artificial graphite A was mixed with 8.8 kg of anthracene oil in a fusion machine for 10 min, and heat-treated at 610° C. in a horizontal kettle for 12 h to obtain single-particle artificial graphite B.

[0096] (3) 15 kg of single-grain artificial graphite B and 1.65 kg of anthracene oil were mixed uniformly in a fusion machine for 10 min, and carbonized in a roller kiln at 1400° C. for 12 h to obtain a composite graphite coated product.

[0097] (4) Weigh 1.5 kg of the composite graphite coated product and 300 g of a 0.67 M sodium maleate solution (pH = 7), mix them evenly, and then pour them into a fusion machine. Adjust the main machine speed to 1200 r / min and the fusion frequency to 40 Hz. After fusion for 10 minutes, dry them at 110° C. in a blast drying oven to obtain a graphite composite material.

[0098] Figure 1 Schematic diagram of the structure of graphite composite material.

[0099] Example 2

[0100] The difference between this embodiment and embodiment 1 is that the concentration of sodium maleate in step (2) is 0.33M.

[0101] Example 3

[0102] The difference between this embodiment and embodiment 1 is that the salt solution in step (2) is sodium acrylate and the solution concentration is 0.67M.

[0103] Example 4

[0104] The difference between this embodiment and embodiment 1 is that the salt solution in step (2) is sodium acrylate and the solution concentration is 0.33M.

[0105] Example 5

[0106] (1) 80 kg of the single-particle artificial graphite A obtained in Example 1 and 5.2 kg of XM with a D50-5 μm and a residual carbon value of 46% produced by Liaoning Xinde Factory were mixed in a VC mixer at 20 Hz for 60 min, and heat-treated in a horizontal kettle at 610° C. for 12 h to obtain single-particle artificial graphite B.

[0107] (2) 15 kg of single-grain artificial graphite B and 1.65 kg of anthracene oil were mixed uniformly in a fusion machine for 10 min, and carbonized in a roller kiln at a temperature of 1350° C. for 12 h to obtain a composite graphite coated product.

[0108] (3) Weigh 1.5 kg of composite graphite coated product and 300 g of 0.67 M sodium maleate solution (pH = 7), mix them evenly, and then pour them into a fusion machine. Adjust the main machine speed to 1200 r / min and the fusion frequency to 40 Hz. After fusion for 6 minutes, dry them in a blast drying oven at 110°C.

[0109] Example 6

[0110] The difference between this embodiment and embodiment 5 is that the asphalt in step (1) is isotropic asphalt produced by Capone (softening point > 140°C, coking value 42%), and the amount used is 5.6 kg.

[0111] Example 7

[0112] The difference between this embodiment and embodiment 1 is that in step (3), anthracene oil is replaced by phenolic resin (softening point is ∼140° C., coking value is ∼40%), and the amount used is 0.75 kg.

[0113] Comparative Example 1

[0114] The difference between this embodiment and embodiment 1 is that the concentration of sodium maleate in step (2) is 0.1 M.

[0115] Comparative Example 2

[0116] The difference between this embodiment and embodiment 1 is that the carbonization temperature in step (3) is 1050°C.

[0117] Comparative Example 3

[0118] The difference between this embodiment and embodiment 1 is that the salt solution in step (2) is sodium acrylate and the solution concentration is 0.1M.

[0119] Comparative Example 4

[0120] The difference between this comparative example and Example 1 is that the amount of anthracene oil added in step (2) is 17.6 kg, and after the heat treatment, carbonization is continued in a roller kiln at 1350° C. to obtain a primary composite graphite coated product.

[0121] Comparative Example 5

[0122] The difference between this comparative example and Example 5 is that the amount of anthracene oil used in step (2) is 3.3 kg.

[0123] Effect Example 1

[0124] The graphite composite materials prepared in Examples 1 and 2 were tested for particle size, tap density, BET specific surface area, etc., and the results are shown in Table 1. The instruments used for the test were: laser particle size distribution analyzer MS2000, tap compactor TF-100B, specific surface area tester NOVA Toμch 2000 and FT-100F powder automatic compaction density meter.

[0125] Figure 2 is a particle size distribution curve of the graphite composite material prepared in Example 1, Figure 3 This is the SEM image of the graphite composite material prepared in Example 1.

[0126] The half-cell manufacturing method is as follows: weigh the graphite sample, conductive carbon black SP, CMC and SBR according to the mass ratio of 95:2:1.5:1.5, stir them in water to form a slurry, apply the slurry to both sides of the copper foil using a coater, put the electrode sheet coated on both sides into a vacuum drying oven at a temperature of 110°C for 2 hours, and then press it into a negative electrode. The compaction density is 1.6g / cm 3 CR-2420 button cells were made in a Mikaelona glove box under nitrogen conditions. The electrolyte was 1M LiPF6+EC:EMC:DNC=1:1:1 (V:V:V). The negative electrode was metal. Charge and discharge tests were carried out on a blue battery test cabinet with a voltage range of 0.005-1.0V and a charge and discharge rate of 0.1C. The first discharge capacity a0 was obtained.

[0127] The rate, DC impedance and AC impedance tests were performed on an American Arbin 2000 battery tester with a voltage range of 0.005 to 1.0V.

[0128] 2C constant / 0.1C total rate test method: The button battery 2C fast discharge constant current ratio test uses a button battery that has been cycled at 0.1C for 3 weeks at 25±5℃. It is now charged to 1V at 0.1C, then discharged to 5mV at 2C to obtain capacity a, and then discharged to 5mV at 0.1C to obtain capacity b. 2C fast discharge constant current ratio = a / (a+b)*100%.

[0129] Test method for capacity retention rate after 7-day storage at 60°C: bake the battery in a 60°C oven for 7 days, then use a current of 0.1C for charge and discharge test to obtain capacity c, 60°C capacity retention rate (%) = c / a0*100%.

[0130] The test method of direct current resistance (DCIR) is as follows: the half-battery is charged once at 0.1C charge and discharged once at 0.2C discharge at 25°C, and its voltage drop is measured at SOC80 (based on 100% of the entire battery charge capacity, charged to 80% of the charge capacity) by the current flowing at 2C for 10 seconds (V) and the voltage difference between the voltage (V) generated by the current flowing at 0.2C for 10 seconds to obtain the direct current internal resistance (DCIR).

[0131] Table 1 Physical, chemical and electrical properties of materials

[0132]

[0133]

[0134] As can be seen from Table 1, in Examples 1, 2 and Comparative Example 1, as the content of small molecule salts decreases, the gram capacity remains at the same level, the first discharge efficiency decreases slightly, and the rate decreases. In Examples 5 and 6, the first coating layer is coated with asphalt, and the gram capacity and first discharge efficiency are at the same level as in Example 1, and the rate of Example 5 is slightly lower. In Example 7, the second coating material is phenolic resin, and its first discharge efficiency and rate are reduced compared with Example 1. In Comparative Example 2, the carbonization temperature decreases, resulting in a decrease in the first discharge efficiency, indicating that high-temperature coating is beneficial to improving the first discharge efficiency.

[0135] Comparative Example 4 uses a primary coating method, and the amount of coating agent used is the same as the total amount of secondary coating used in Example 1. Compared with Example 1, its gram capacity, first discharge efficiency and 60°C capacity retention rate are all reduced, indicating that the secondary coating can make the coating layer more uniform, improve the first discharge efficiency and cycle performance. Comparative Example 5 increases the amount of the second coating agent anthracene oil compared to Example 5, and the first discharge efficiency and rate are significantly reduced, while the particle size increases, indicating that the increase in the amount of coating agent causes the coating uniformity to decrease.

[0136] The above embodiments are preferred implementation modes of the present invention, but the present invention is not limited to the specific implementation modes disclosed and described above, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.

Claims

1. A graphite composite material, characterized in that: A coating layer containing an organic small molecule salt is wrapped around the outer layer of the composite graphite coating; the content of the organic small molecule salt is 0.5-2wt%, and % refers to the mass percentage of the organic small molecule salt in the composite graphite coating; The organic small molecule salt is sodium maleate; The preparation method of the composite graphite coated product comprises the following steps: (1) A mixture of single-particle artificial graphite A and coating agent A is subjected to heat treatment to obtain single-particle artificial graphite B; the coating agent A is anthracene oil; the amount of the coating agent A is 1-11wt%; % refers to the mass percentage of the coating agent A in the single-particle artificial graphite A; the heat treatment temperature is 550°C-650°C; (2) A composite graphite coated product is prepared by carbonizing a mixture of a single-particle artificial graphite B and a coating agent B; the coating agent B is anthracene oil; the amount of the coating agent B is 1-11wt%; % refers to the mass percentage of the coating agent B in the single-particle artificial graphite B; the carbonization temperature is 1400-1700°C.

2. The graphite composite material according to claim 1, characterized in that In step (1), the particle size of the single particle artificial graphite A is 7-12 μm; And / or, in step (1), the single particle artificial graphite A can be prepared by graphitizing aromatic petroleum coke; and / or, when the coating agent A and the coating agent B contain anthracene oil, the coking value of the anthracene oil in the coating agent A and the coating agent B is 11-20%; and / or, when the coating agent A and the coating agent B contain anthracene oil, the residual carbon value of the anthracene oil in the coating agent A and the coating agent B is 0.5-2wt%; And / or, in step (1), the heat treatment temperature is 600-650°C; And / or, in step (1), the heat treatment time is 4 to 12 hours; And / or, in step (1), the heat treatment further includes fusion treatment before the heat treatment; And / or, in step (2), the carbonization temperature is 1400°C; And / or, in step (2), the carbonization time is 10 to 14 hours; And / or, in step (2), the carbonization further includes a fusion treatment.

3. The graphite composite material according to claim 2, characterized in that In step (1), the particle size of the single particle artificial graphite A is 9 μm; And / or, in step (1), the heat treatment temperature is 610°C; And / or, in step (1), the heat treatment time is 12 hours; And / or, in step (2), the carbonization time is 12 hours.

4. The graphite composite material according to claim 2, characterized in that: In step (1), the graphitization operation also includes a pre-carbonization treatment; And / or, in step (1), the type of aromatic petroleum coke is green coke; And / or, in step (1), the aromatic petroleum coke further includes a pretreatment process of crushing and premixing before graphitization; And / or, in step (1), the graphitization temperature is 2800-3050°C; And / or, in step (1), the graphitization time is 15 to 25 days; And / or, in step (1), the graphitization processing cycle is 35 to 45 days; And / or, in step (1), the fusion time is 5 to 30 minutes; And / or, in step (2), the fusion time is 5 to 30 minutes.

5. The graphite composite material according to claim 4, characterized in that The pre-carbonization temperature is 600-1300°C; And / or, the pre-carbonization time is 3 to 27 days; And / or, in step (1), the type of aromatic petroleum coke is Daqing petroleum green coke; And / or, before the pretreatment, the specifications of the aromatic petroleum coke are volatile matter ≤ 16%, ash content ≤ 0.4%; And / or, after the pulverization process, the particle size D50 of the aromatic petroleum coke is 0-50 μm; And / or, after the pulverization, the tap density of the aromatic petroleum coke is 0.5-1.3 g / cm 3 ; And / or, in step (1), the graphitization temperature is 3000°C; And / or, in step (1), the graphitization time is 500h; And / or, in step (1), the graphitization processing cycle is 40 days; And / or, in step (1), the fusion time is 10 min; And / or, in step (2), the fusion time is 10 minutes.

6. The graphite composite material according to claim 5, characterized in that The pre-carbonization temperature is 1050°C; And / or, the pre-carbonization time is 4 days; And / or, after the pulverization process, the particle size D50 of the aromatic petroleum coke is 9-10 μm; And / or, after the pulverization, the tap density of the aromatic petroleum coke is 0.5-1.1 g / cm 3 .

7. The graphite composite material according to claim 6, characterized in that After the pulverization process, the particle size D50 of the aromatic petroleum coke is 9.1 μm; And / or, after the pulverization, the tap density of the aromatic petroleum coke is 0.54 g / cm 3 .

8. A method for preparing a graphite composite material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: uniformly mixing the composite graphite coated product and the solution of the organic small molecule salt; the relative molecular weight of the organic small molecule salt is less than 500.

9. The method for preparing the graphite composite material according to claim 8, characterized in that: The organic small molecule salt solution has a concentration of 0.1 to 1 mol / L in terms of small molecule salt; And / or, in the solution of the organic small molecule salt, the concentration of the composite graphite coated product is 20-40wt%, % refers to the mass ratio of the composite graphite coated product to the organic small molecule salt solution; and / or, the pH of the solution of the organic small molecule salt is neutral; And / or, the mixing method is to mix uniformly through a fusion process.

10. The method for preparing the graphite composite material according to claim 9, characterized in that: In the solution of the organic small molecule salt, the concentration is 0.1-0.67 mol / L in terms of small molecule salt.

11. The method for preparing a graphite composite material according to claim 10, characterized in that: In the solution of the organic small molecule salt, the concentration is 0.1 mol / L, 0.33 mol / L or 0.67 mol / L mol / L, calculated as the small molecule salt.

12. The method for preparing the graphite composite material according to claim 9, characterized in that: The concentration of the sodium maleate solution is 0.1~0.7M; And / or, the fusion frequency is 40 Hz; And / or, the main engine speed of the fusion is 1200r / min; And / or, the fusion time is 5 to 30 minutes; And / or, the fusion process further includes a post-process of heating and drying.

13. The method for preparing a graphite composite material according to claim 12, characterized in that: The concentration of the sodium maleate solution is 0.1M, 0.33M or 0.67M; And / or, the fusion time is 6 min or 10 min; And / or, the drying method is vacuum drying or forced air drying.

14. The method for preparing a graphite composite material according to claim 13, characterized in that: When the drying method is vacuum drying, the drying temperature is 80-110°C; Alternatively, when the drying method is air drying, the air drying temperature is 70-130°C.

15. The method for preparing a graphite composite material according to claim 14, characterized in that: When the drying method is vacuum drying, the drying temperature is 105°C; Alternatively, when the drying method is air drying, the air drying temperature is 110°C.

16. A graphite composite material, characterized in that: The graphite composite material is prepared by the preparation method of any one of claims 8 to 15.

17. Use of the graphite composite material as claimed in claim 16 as a negative electrode material in a lithium ion battery.

Citation Information

Patent Citations

  • A method for modifying graphite anode materials for lithium-ion batteries

    CN105514394B

  • Preparation method of asphalt liquid phase coated modified artificial graphite lithium battery cathode material

    CN103682350A

  • Power lithium-ion battery negative electrode material with core-shell structure and preparation method thereof

    CN103811717A

  • Modification method for lithium-ion battery graphite cathode material

    CN105514394A